Giant Cell Tumor of Capitate with Secondary Aneurysmal Bone Cyst: A Case Report - Ramanujapuram, Suneel; Parameswaran, Apurve; Perubhotla, Lakshmi Manasa; Mohammed, Murtuza Ahmed; Shah, Harshil Nitinkumar; Eachempati, Krishna Kiran (Journal of Wrist Surgery, 2024)
Giant cell tumors (GCTs) of the carpal bones are rare. GCTs of the hand tend to be aggressive, could result in multifocal presentation, and have a high rate of recurrence.We report a rare case of GCT of the capitate with secondary aneurysmal bone cyst (ABC) in a 40-year-old man. The patient presented with complaints of pain and swelling over his right wrist since 6 months. Radiographs showed the presence of a lytic lesion in the capitate. Magnetic resonance imaging scanning revealed a well-defined, lobulated, multiseptate lytic lesion involving the entire capitate, extending into its subarticular regions. Fine-needle aspiration revealed findings suggestive of a GCT. He underwent en-bloc excision of the capitate, bone grafting of the defect using an appropriately sized bicortical iliac crest autograft, and third carpometacarpal and midcarpal fusion. Histopathological examination of the lesion confirmed the presence of a GCT, with a secondary ABC. At 3 years following surgery, he was asymptomatic with no signs of tumor recurrence, radiocarpal arthritis, or instability. He was able to perform 45 and 60 degrees of wrist extension and flexion, respectively.To our knowledge, there are no prior reported cases of GCT of the capitate with a secondary ABC.GCTs of the hand in general have a high rate of recurrence. The presence of a super-added ABC could further increase this risk. In the authors' opinion, en-bloc excision of the affected bone, reconstruction of the defect, and appropriate fusion is the optimal mode of management of these cases.
Keywords: giant cell tumor; secondary aneurysmal bone cyst; capitate; carpal bone tumor